CLONING AND CHARACTERIZATION OF ISOLATED TAQ DNA POLYMERASE GENE FROM PHAGE - MISHRA, NIKHIL; KUMAR, ANIL (The Bioscan, 2009)
Taq polymerase is a thermo stable DNA polymerase named after the thermophilic bacterium T.aquaticus, having a molecular weight of 66,000-94,000 Daltons. Taq DNA polymerases have become a valuable tool in today’s research. The choice of the DNA polymerase is determined by the goals of the experiment. We have isolated Taq DNA polymerase gene (2500 bp) from phage (PHI4-2) genomic DNA (USA) and cloned into a salt inducible bacterial expression vector (PUB-S-X-CH2) and the recombinant vector was transformed into BL21 (DE3) pLysS competent cells and screened for the presence of the insert in right orientation. The expression of Taq gene using salt inducible expression vector makes the production of Taq DNA polymerase enzyme much cheaper as compared to IPTG inducible expression systems.